Pembuatan Karbon Aktif Secara Kimia Hijau Dari Limbah Cangkang Kelapa Sawit (Elaeis guineensis) Dengan Aktivator Microwave - Muhammad Taufik; Tirta Suci Dian Kasih; Miftahul Khair (Jurnal Periodic Jurusan Kimia UNP, 2021)
Activated carbon from palm kernel shell has been prepared by using microwave assisted activation. Carbonization was conducted at mild condition of 400ºC for 90 minutes heating time. Microwave irradiation 300 Watt for 2 minutes with frequency 2.45 GHz increase s the carbon iodine number from 452.4021 mg / g up to 829.4040 which is higher than SNI 06-3730-1995 requirement of 750 mg / g for activated carbon. FTIR spectra results show that activated carbon has - OH groups at wave numbers of 3000-3500 cm -1 , C = C at wave numbers of 1550-1650 cm -1 , C - O at wave numbers of 1000-1260 cm -1 and C - H at wave numbers of 810-770 cm -1 . Adsorption test results showed that the prepared activated carbon was able to absorb Pb+2 ion at the optimum concentration of 8 0 mg / L. Adsorption isotherms study conducted by the Langmuir equation produces a regression coefficient R 2 = 0.8903 with a maximum of adsorption capacity of 13.3868 mg / g.